Internet communications in the information society: socio-cultural aspects - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article is devoted to the study of the peculiarities of Internet communications functioning in the information age. The aim and tasks. Internet communications invasion in the life of humanity causes the virtual reality, which significantly changes the forms of human relations. Instead of personal meetings and direct communication, people get used to communicating in virtual space, which affects their professional activity, study, leisure, and other kinds of activity. Therefore, it is necessary to study the peculiarities of functioning of new forms of Internet communications and their impact on the development of society. Research methods. The theoretical and methodological basis of the research is general scientific and special methods and approaches by which the dynamics of changes in the communication system in the conditions of the information society is investigated. One such approach is a synergistic system approach. Research results. With regard to scientific communication and education, successful creative interaction of scientists in their work nowadays largely depends on the level of information culture (network etiquette, etc) of scientists, researchers, teachers and students and their ability to use the latest information and communication technologies. In this case, information technology acts as an instrumental knowledge. Also, social networking is becoming a powerful tool for influencing people's public opinion. Discussion. Nowadays, when access to information is provided by the latest information and communication technologies, there are some difficulties in using Internet communications in education and science. These include, first of all, the availability of technical support (computers, modems, etc.) in educational and scientific institutions, the almost complete lack of a methodological base for the use of the latest technologies in education, the need for the creation of electronic libraries and more. Conclusion. Internet communications form their own socio-cultural space, becoming an integral part of all spheres of human life, gradually replacing the process of real communication with the virtual one. Currently, functioning of social networks is important not only for organizing personal contacts, leisure, but also for providing professional connections, education and more.